Biomechanical Analysis of First Serve Tennis - Rumi iqbal Doewes; Islahuzzaman Nuryadin (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2022)
Serve tennis is the most important stroke in the game of tennis to determine the outcome of the match, which is done by means of the ball crossing the net into the opponent's service box diagonally with the desired speed and landing location. This study aims to explain the biomechanical analysis of first serve tennis which produces maximum ball speed. The research method is in the form of quantitative biomechanics with an inferential analysis approach in the form of correlation analysis. Twelve students of the Department of Sports Coaching, Faculty of Sport, made a first serve at the service box, the movements were recorded using a Canon EOS 1100D DSLR camera. The variables analyzed were flexion angle, extension angle, tilt angle, angular velocity, angular acceleration, time, momentum, force, impulse, power, and effort. Pearson Correlation is used to show how big the correlation between ball speed and the studied biomechanics variables. The results showed that there was a large, very large, and perfect correlation on the variables of momentum (r = 1,000), force (r = .663), impulse (r = 1,000), power (r = .844), effort (r = . 982), while the other variables show very small, small, and moderate correlations. So it can be concluded that first serve tennis can be seen as a coordinated and complex movement, involving the development and transfer of momentum, force, impulse, power, and effort to achieve maximum ball speed. This study implies that in doing first serve tennis, it is necessary to pay attention to momentum, force, impulse, power, and effort to produce maximum ball speed.